The Principle of Legality and Compulsory Criminal Prosecution. Myth and Reality (Justicia &Derecho, 2025)
The article—from a comparative law perspective—the interpretation of the principle of legality in criminal prosecution, highlighting that, due to limited resources, prosecuting authorities must select cases to investigate based mainly on the severity of the crime, the likelihood of success, and the social expectations involved in criminal law enforcement. Effective management requires this selection procedure, but it shouldn’t be capricious or go against the legality principle, which calls for fair prosecution.  The principle of legality requires that similar cases be treated uniformly and that investigations not be omitted without reasonable justification. The writing also says it’s wrong for prosecutors to “resign” when crimes are small or hard to investigate, because this could go against the idea of law. It concludes by saying that in order for the system to meet justice standards and guarantee the efficacy of criminal prosecutions, criminal reforms should be accompanied by an increase in resources.
Keywords: selection of cases; principle of legality; criminal law enforcement; criminal prosecution; preclassification mechanisms